2006
DOI: 10.1002/masy.200651033
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Release of Model Drug from Biodegradable Segmented Polyurethane Ureas: Morphological and Structural Features

Abstract: Summary: Segmented polyurethane ureas (SPUUs), which are being used in implant devices, were evaluated as drug delivery matrices using theophylline as a model drug without much sacrificing the mechanical properties of films after drug doping. SPUUs were synthesized from aliphatic diisocyanate (lysine methyl ester diisocyante (LDI)), poly(caprolactone) diol with molecular weights 530, 1250 and 2000 and 1,4-butanediamine. Three series of segmented SPUUs were prepared with various soft segment lengths and were ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 15 publications
1
24
0
Order By: Relevance
“…The maximum in the loss modulus (E′′) at low frequencies is, however, very close to T g . From Figure 2, the temperature corresponding to E′′, very close to T g as obtained from DSC reported elsewhere, 18 was found to be ∼-19°C for the parent polymer. In the semi-IPN systems, the effect of PNiPAAm content on the PCL(530)(50)LDI-BDA network is observed as variation of T g compared to the parent system.…”
Section: Resultssupporting
confidence: 83%
“…The maximum in the loss modulus (E′′) at low frequencies is, however, very close to T g . From Figure 2, the temperature corresponding to E′′, very close to T g as obtained from DSC reported elsewhere, 18 was found to be ∼-19°C for the parent polymer. In the semi-IPN systems, the effect of PNiPAAm content on the PCL(530)(50)LDI-BDA network is observed as variation of T g compared to the parent system.…”
Section: Resultssupporting
confidence: 83%
“…Reddy et al (2006) found that the release of drugs from those synthesized polyurethanes can be explained by the Fickian diffusion model.…”
Section: Polyurethane For Drugcontrolled Deliverymentioning
confidence: 96%
“…They have a prolific effect on microbicidal and biofilm inhibition activity, biocompatibility, and drug targeting . Hyperbranched polyurethane (HBPU) is a well‐known wound healing material and potent drug carrier . Its application, along with Fe 3 O 4 –MWCNT NH to form Fe 3 O 4 –MWCNT NH/HBPU nanocomposites (NNCs), has been explored in the development of effective wound healing material.…”
Section: Nanoengineered Antibiotic Delivery Systemsmentioning
confidence: 99%